Analysis of Word Order Errors in Indonesian Students’ Chinese Writing: 印尼学生汉语书面语语序偏误分析 - Vinnie Hidayat; Lysa Lho (Mandarinable: Journal of Chinese Studies, 2026)
Word order is an essential grammatical device in daily Chinese expression. The arrangement of words follows fixed rules and cannot be arbitrary. A preliminary survey reveals that Chinese word order errors are prevalent in the written production of students at the Harapan Bersama Language Institute. This study aims to identify most common types and causes of word order errors among the 2024 undergraduate cohort. Using corpus collection and questionnaire surveys, it systematically analyzes their errors. Results show that errors fall into seven categories: subject-predicate, predicate-object, attributive-head, adverbial-head, predicate-complement, function word, and others. Among these, adverbial-head errors are the most frequent, accounting for 55.7% and representing the main learning difficulty, while predicate-object errors are the least at 2.6%. The causes are attributed to differences between Indonesian and Chinese word order, learner internal factors (including L1 negative transfer, overgeneralization, inappropriate learning/communication strategies, and individual traits), and teacher-related aspects. This study hopes to serve as a reference for Chinese word order instruction and learning.